House prices and financial liberalisation in Australia - Williams, D (University of Oxford, 2009)
Financial liberalisation and innovation (FLIB) in Australia over the 1980s and 1990s provided the institutional backdrop for one of the most rapid increases in household balance sheets and house prices in the world. An equilibrium correction model of quarterly Australian house prices for 1972-2006 identifies the key long run drivers as real non-property income per house, the working age population proportion, the unemployment rate, two government policy changes, real and nominal interest rates and non-price credit conditions. All else equal, easing credit supply conditions attributable to FLIB directly raised the long run level of real house prices by around 51 per cent while higher real interest rates subtracted 29 per cent from long run prices. Real interest rates are shown to have a significant impact on real house prices after financial liberalisation but play no role before. These findings suggest that FLIB fundamentally relaxed binding credit constraints on households and enhanced opportunities for intertemporal smoothing. The model also explicitly captures short run overshooting dynamics in Australian house prices. Whenever lagged real house price growth is greater than about 4 per cent, for example during booms, house prices tend to display "frenzy" behaviour measured as a cubic of lagged house price changes.